2022
DOI: 10.1002/vms3.721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary stinging nettle (Urtica dioica) on hormone stress and selected serum biochemical parameters of broilers subjected to chronic heat stress

Abstract: Background: Heat stress is one of the most critical problems confronting the poultry industry. Stinging nettle (SN) is a medicinal plant with potent antioxidant properties. Objective:The goal of this study was to evaluate the effects of dietary SN at two different levels (2 and 4%) on the serum levels of cortisol and some selected parameters of broilers exposed to chronic heat stress.Methods: A total of 240 broiler chickens were randomly assigned to six dietary groups as follows: (1) control: fed the basal die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…While not reaching our FDR < 0.05, cutoff, the transcript levels encoding three other enzymes critical to cholesterol synthesis were elevated under heat stress including: 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGCR; HS mean FPKM = 191.4, TN FPKM mean = 122.9); 24-Dehydrocholesterol Reductase (DHCR24; HS mean FPKM = 54.1, TN FPKM mean = 39.7) and 7-Dehydrocholesterol Reductase (DHCR7; HS mean FPKM = 136.2, TN FPKM mean = 97.7). The increase in the transcripts encoding these genes is consistent with reports of cholesterol levels increasing during heat stress [ 56 58 ]. As mentioned above, DNAJA4 also affects cholesterol metabolism by increasing HMGCR protein levels [ 20 ].…”
Section: Resultssupporting
confidence: 90%
“…While not reaching our FDR < 0.05, cutoff, the transcript levels encoding three other enzymes critical to cholesterol synthesis were elevated under heat stress including: 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGCR; HS mean FPKM = 191.4, TN FPKM mean = 122.9); 24-Dehydrocholesterol Reductase (DHCR24; HS mean FPKM = 54.1, TN FPKM mean = 39.7) and 7-Dehydrocholesterol Reductase (DHCR7; HS mean FPKM = 136.2, TN FPKM mean = 97.7). The increase in the transcripts encoding these genes is consistent with reports of cholesterol levels increasing during heat stress [ 56 58 ]. As mentioned above, DNAJA4 also affects cholesterol metabolism by increasing HMGCR protein levels [ 20 ].…”
Section: Resultssupporting
confidence: 90%
“…The physiological response to HS in poultry involves the activation of the sympathetic adreno-medullary ( SAM ) pathway that results in the release of catecholamines, such as epinephrine and norepinephrine, and then activation of the hypothalamic–pituitary–adrenal ( HPA ) axis that results in the secretion of glucocorticoids ( GC ) ( Li et al, 2022 ; Mirsaiidi Farahani and Hosseinian, 2022 ; Oluwagbenga et al, 2022 ). Several studies have reported the detrimental effect of prolonged exposure to GC resulting from HS on production, performance, egg quality and welfare of the exposed animal ( Mashaly et al, 2004 ; Ebeid et al, 2012 ; Ma et al, 2014 ; Mehaisen et al, 2019 ; Qin et al, 2023 ; Welay et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological responses to stress in poultry involve the activation of the SAM pathway that results in the release of catecholamines such as epinephrine ( EP ) and norepinephrine ( NE ) from the adrenal medulla ( Li et al, 2022 ). After the SAM, the HPA axis is activated which results in the release of GC, such as cortisol and corticosterone from the adrenal cortex ( Li et al, 2022 ; Mirsaiidi Farahani and Hosseinian, 2022 ; Oluwagbenga et al, 2022 ). Historically, cortisol and corticosterone were believed to be the major stress hormones in birds; however, over the past 20 years cortisol has been given considerably less attention in birds with corticosterone being the focus of research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HPI axis, on the other hand, is involved in the reallocation of resources to increase the supply of glucose in the blood by increasing catabolic pathways and depressing other energetically costly processes such as immune responses and reproduction. The HPI axis activation culminates in the release of glucocorticoids from internal cells located in the head kidney [ 27 ], leading to production of corticosteroids, primarily cortisol [ 24 , 28 ].…”
Section: Introductionmentioning
confidence: 99%